THE ROLE OF ARTIFICIAL INTELLIGENCE (AI) IN ESSAY WRITING - Male, Hendrikus; Timu, Thereza Melani; Sabrina, Debora (SIGEH ELT : Journal of Literature and Linguistics, 2025)
The rapid development of Artificial Intelligence (AI) has led to its widespread adoption in education, particularly in essay writing. AI-powered tools such as ChatGPT and Grammarly may assist students in various aspects of writing, including grammar correction, idea generation, and content refinement. This study explores students' perceptions of AI's role in essay writing, its benefits, and potential challenges related to academic integrity, creativity, and time management. Using a qualitative research design, semi-structured interviews were conducted with five students enrolled in an essay writing class. Thematic analysis of the data revealed that students generally perceive AI as a beneficial tool that enhances writing efficiency, provides instant feedback, and improves the technical aspects of writing. However, some participants expressed concerns about losing their personal writing style and becoming overly reliant on AI, which may hinder creativity and independent thinking. Additionally, issues related to academic integrity emerged, with students questioning whether AI-generated assistance could be considered plagiarism. Additionally, AI's impact on students' time management differed, as some experienced greater productivity, while others acknowledged increased procrastination due to AI's capacity to accelerate tasks.The findings suggest that while AI offers significant advantages, it should be used responsibly as a supportive tool rather than a substitute for independent writing skills. Educational institutions should establish clear guidelines to promote ethical AI usage and encourage students to balance AI assistance with personal effort to develop critical thinking and originality in writing.The rapid development of Artificial Intelligence (AI) has led to its widespread adoption in education, particularly in essay writing. AI-powered tools such as ChatGPT and Grammarly may assist students in various aspects of writing, including grammar correction, idea generation, and content refinement. This study explores students' perceptions of AI's role in essay writing, its benefits, and potential challenges related to academic integrity, creativity, and time management. Using a qualitative research design, semi-structured interviews were conducted with five students enrolled in an essay writing class. Thematic analysis of the data revealed that students generally perceive AI as a beneficial tool that enhances writing efficiency, provides instant feedback, and improves the technical aspects of writing. However, some participants expressed concerns about losing their personal writing style and becoming overly reliant on AI, which may hinder creativity and independent thinking. Additionally, issues related to academic integrity emerged, with students questioning whether AI-generated assistance could be considered plagiarism. Additionally, AI's impact on students' time management differed, as some experienced greater productivity, while others acknowledged increased procrastination due to AI's capacity to accelerate tasks.The findings suggest that while AI offers significant advantages, it should be used responsibly as a supportive tool rather than a substitute for independent writing skills. Educational institutions should establish clear guidelines to promote ethical AI usage and encourage students to balance AI assistance with personal effort to develop critical thinking and originality in writing.